The Effect of Digital Transformation on Human Resource Management: Empirical Study From the Department of Culture and Tourism of South Sumatera Province, Indonesia - Sari, Mayang Alya; Halin, Hamid; Afriyani, Fauziah (Golden Ratio of Human Resource Management, 2025)
This study aims to analyze the influence of digital transformation on human resource management at the Department of Culture and Tourism of South Sumatra Province. Digital transformation is key to improving operational efficiency, team member productivity, and data-based decision making. The research method used is quantitative with a simple linear regression analysis technique. Data were collected through questionnaires distributed to department employees as research respondents. The study results show that digital transformation positively and significantly affects human resource management. The implementation of digital technology contributes to increasing employee work effectiveness, optimizing information systems, and managing human resources that are more adaptive to change. Thus, the department needs to continue improving its digitalization strategy through training and developing digital competencies for its employees to optimize the benefits of digital transformation.